Influence of tobacco smoking on oral health - Kuchta, Ewa; Berger, Marcin; Trafidło, Piotr; Szymańska, Jolanta (Polish Journal of Public Health, 2013)
Tobacco smoking is considered the most frequent addiction both in Poland and all over the world. Tobacco smoke contains about 4,000 chemical compounds, 40 of which are carcinogens. Tobacco smoking leads to deterioration of the oral cavity condition, exerts a harmful influence on the oral mucosa and is considered as one of the most important risk factors in the development of oral cancer. The substances contained in tobacco smoke cause tissue anoxia, which negatively affects wound healing and mucosa regeneration. Local application of high temperature results in burns and ulceration in the mucosa. The reduced salivation observed in smokers facilitates the development of caries, fungal infections and periodontitis. Smoking leads to an increased growth of the bacterial flora pathogenic for the periodontium, affects tissue protective mechanisms, causes an increase in dental loss and bone destruction in the alveolar process. Smokers undergoing implant prosthetic treatment face a greater risk of the peri-implant tissue inflammation and implant failure. Moreover, changes in the colour of teeth, mucosa, fillings and implants, as well as halitosis and taste disorders, are observed in smokers. Smoking cessation results in the reversal of most described symptoms. The dentist is often the first person to perceive the problem related to the consequences of smoking. The greatest risk for the oral health posed by smoking is oral cancer. It is thus necessary for dentists to remain alert to the signs of cancer to enable its early diagnosis. The task of the whole dental team is to educate patients on the harmful influence of cigarette smoking on health and life, making them aware of the relationship between smoking and the changes in the oral cavity, and to support them in their struggle with addiction